2014
DOI: 10.1021/cg501500w
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth Behavior of Methane Hydrate in the Presence of Liquid Hydrocarbon

Abstract: This paper reports the visual observation of the formation and growth of methane hydrate crystals in the methane + decane + water three-phase quiescent system. This three-phase system is a simplified model of the condition within an oil-producing pipeline. A hydrate crystal nucleated at a random point on the water droplet surface and then became a hydrate film that covered the whole surface of the water droplet. The morphology of individual hydrate crystals grown at the water droplet surface were triangular or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The termination of hydrate formation and growth after coverage of the gas/liquid interface would be caused by elimination of the contact between methane and the MPD aqueous solution by the hydrate crystals formed at the interface. The macroscopic growing mechanism of methane-MPD hydrate under these conditions is distinct from that of other general hydrates which form at the gas/liquid interface. ,, For instance, in the methane-water system, a relatively limited number of hydrate crystals were formed at the gas/water interface and covered the interface growing along the interface, whereas numerous small methane-MPD hydrate crystals filled up the interface with frequent nucleation rather than growth of the individual hydrate crystals. In other words, hydrate crystals did not form a film but an agglomeration of small crystals at the interface in the methane-MPD-water system.…”
Section: Resultsmentioning
confidence: 96%
“…The termination of hydrate formation and growth after coverage of the gas/liquid interface would be caused by elimination of the contact between methane and the MPD aqueous solution by the hydrate crystals formed at the interface. The macroscopic growing mechanism of methane-MPD hydrate under these conditions is distinct from that of other general hydrates which form at the gas/liquid interface. ,, For instance, in the methane-water system, a relatively limited number of hydrate crystals were formed at the gas/water interface and covered the interface growing along the interface, whereas numerous small methane-MPD hydrate crystals filled up the interface with frequent nucleation rather than growth of the individual hydrate crystals. In other words, hydrate crystals did not form a film but an agglomeration of small crystals at the interface in the methane-MPD-water system.…”
Section: Resultsmentioning
confidence: 96%
“…However, crystal growth characteristics due to the soluble guest gas composition in the aqueous bulk liquid phase are an important factor that should be considered during the process design of the CO 2 –CH 4 gas separation via a hydrate-based crystallization route. The literature reports morphological studies for different natural gas mixtures at different concentrations, ,,− morphological studies conducted in different types of reactors that provide different gas–liquid contact modes for different gas hydrate systems, , morphological studies of methane hydrate systems using kinetic promoters like surfactants and amino acids, ,, and morphological studies of methane hydrate formation in the presence of a hydrophobic guest liquid as an additive. , Smelik and King investigated the hydrate crystal growth behavior of sI, sII, and sH hydrates and observed that sI, sII, and sH hydrate structures bears their own characteristic hydrate crystal morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrates or clathrate hydrates (denominated “hydrates” hereafter), are solid solutions composed of water molecules called the “host” that form cages by hydrogen bonds and enclose different molecules called “guests” within the cages; this phenomena occurs, generally, at high pressures and low temperatures (well above the triple point of water). The guest species are small hydrophobic molecules that may be gaseous or liquid at room conditions. , The appearance of hydrate is ice-like (crystalline solid) and it consists of a framework of hydrogen-bonded water molecules, as mentioned earlier. …”
Section: Introductionmentioning
confidence: 99%